Biomass derived carbon for energy storage devices. Issue 6 (13th January 2017) - Wang, Jie; Nie, Ping; Ding, Bing; Dong, Shengyang; Hao, Xiaodong; Dou, Hui; Zhang, Xiaogang
Abstract : Biomass-derived carbon materials have received extensive attention as electrode materials for energy storage devices, including electrochemical capacitors, lithium–sulfur batteries, lithium-ion batteries, and sodium-ion batteries. Abstract : Electrochemical energy storage devices are becoming increasingly more important for reducing fossil fuel energy consumption in transportation and for the widespread deployment of intermittent renewable energy. The applications of different energy storage devices in specific situations are all primarily reliant on the electrode materials, especially carbon materials. Biomass-derived carbon materials are receiving extensive attention as electrode materials for energy storage devices because of their tunable physical/chemical properties, environmental concern, and economic value. In this review, recent developments in the biomass-derived carbon materials and the properties controlling the mechanism behind their operation are presented and discussed. Moreover, progress on the applications of biomass-derived carbon materials as electrodes for energy storage devices is summarized, including electrochemical capacitors, lithium–sulfur batteries, lithium-ion batteries, and sodium-ion batteries. The effects of the pore structure, surface properties, and graphitic degree on the electrochemical performance are discussed in detail, which will guide further rational design of the biomass-derived carbon materials for energy storage devices.